Reviewers of Issue - Journal, HEROS (Helsinki Romanian Studies Journal, 2024)
Tomasz CYCHNERSKI – Adam Mickiewicz University, Poznań, Poland Monica HUȚANU – University of Belgrade, Serbia Ovidiu IVANCU – Vilnius University, Lithuania Ioana JIEANU – University of Ljubljana, Slovenia Aurora MARTIN – Brusov State University, Armenia Roberto MERLO – University of Turin, Italy Silviu Constantin MIHĂILĂ – Bucharest University of Economic Studies, Romania Paul NANU – University of Alba Iulia, Romania Nicoleta NEȘU – Sapienza University of Rome, Italy Petar RADOSAVLJEVIĆ – University of Zagreb, Croatia Annemarie SORESCU-MARINKOVIĆ – Institute of Balkan Studies, Belgrade Justyna TEODOROWICZ – Adam Mickiewicz University, Poznań, Poland Alice TOMA – Université Libre de Bruxelles, Belgium Harieta TOPOLICEANU – University of Turin, Italy Oana URSACHE – Ștefan cel Mare University of Suceava, Romania